Empowerment of Papadak Local Wisdom in Supporting Coastal and Marine Resources Management in Nusak Termanu, Rote Ndao District - LOAINAK, Eny Yurni Anita; NEOLAKA, Melkisedek N.B.C.; TODA, Hendrik (International Journal of Environmental, Sustainability, and Social Science, 2023)
The adoption of Papadak local wisdom to the coastal and marine areas of Rote Ndao Regency was motivated by the increasing destruction of coastal and marine ecosystems, such as the use of destructive fishing gear, the use of bombs and poison, and the increasing number of uncontrolled tourism activities. Efforts to implement this were carried out through various processes involving relevant stakeholders in Rote Ndao Regency, including the Village Government, traditional leaders, religious leaders, youth leaders, community leaders, fishermen and professional representatives. The research method used in this study is a descriptive research method with a qualitative approach, the source of the data in this study was obtained through primary sources and secondary sources. The data that has been collected by interview, observation and document search methods is then analyzed using the spiral data analysis technique proposed by Creswell (2016: 264-268). The empowerment of papadak local wisdom in supporting the management of coastal and marine resources in Nusak Termanu, Rote Ndao Regency was analyzed using the opinion of Latama, Gunarto et.al (2002:4) that community empowerment is considered comprehensive if it displays five characteristics with the conclusion that empowerment of papadak local wisdom in support the management of coastal and marine resources in Nusak Termanu, Rote Ndao Regency; (1) locally based; (2) oriented towards improving welfare; (3) based on partnership but not fulfilling aspects (4) sustainable.